The relationships between exercise intensity, heart rate, and blood pressure during an incremental isometric exercise test - Wiles, J. D.; Allum, S. R.; Coleman, D. A.; Swaine, I. L. (Journal of Sports Sciences, 2008)
Currently, it is not possible to prescribe isometric exercise at an intensity that corresponds to given heart rates or systolic blood pressures. This might be useful in optimizing the effects of isometric exercise training. Therefore, the aim of this study was to explore the relationships between isometric exercise intensity and both heart rate and systolic blood pressure during repeated incremental isometric exercise tests. Fifteen participants performed seated isometric double-leg knee extension, during which maximum voluntary contraction (MVC) was assessed, using an isokinetic dynamometer. From this, a corresponding peak electromyographic activity (EMGpeak) was determined. Subsequently, participants performed two incremental isometric exercise tests (at least 48 h apart) at 10, 15, 20, 25, and 30% EMGpeak, during which steady-state heart rate and systolic blood pressure were recorded. In all participants, there were linear relationships between %EMGpeak and heart rate (r at least 0.91; P < 0.05) and between %EMGpeak and systolic blood pressure (r at least 0.92; P < 0.05). Also, when repeated tests were compared, there were no differences in the slopes (P > 0.50) or elevations (P > 0.10) for either of the relationships. Therefore, these linear relationships could be used to identify isometric exercise training intensities that correspond to precise heart rates or systolic blood pressures. Training performed in this way might provide greater insight into the underlying mechanisms for the cardiovascular adaptations that are known to occur as a result.